Answer: -8/3
Step-by-step explanation:
Multiplying a positive and a negative equals negative: (+)•(-)=(-)
y= - 2/3•4
Y= -8/3
Answer:
c
Step-by-step explanation:
Answer:
x=4
Step-by-step explanation:
if you do you'll get that is 64.
Answer:
1. 30 mins
Step-by-step explanation:
Answer:
Step-by-step explanation:
The sequence above is a geometric sequence.
The common ratio (r) =
The common ratio < 1, therefore, the formula for the sum of nth terms of the sequence would be:
a1 = 3
r = -2
n = 6
Plug in the values into the formula